Using role-play in the EFL classroom to improve speaking skills - Nishanova , Shakhnoza (The Lingua Spectrum, 2024)
This article gives information the role of role-plays in learning foreign language and the productive approaches of teaching through role plays. Also, it provides several important perspectives of role-plays in teaching languages. This can help learners to be able learn languages effectively.